2013
DOI: 10.2967/jnumed.113.126839
|View full text |Cite
|
Sign up to set email alerts
|

The Low Hepatic Toxicity per Gray of 90Y Glass Microspheres Is Linked to Their Transport in the Arterial Tree Favoring a Nonuniform Trapping as Observed in Posttherapy PET Imaging

Abstract: 90 Y resin and glass microsphere liver radioembolizations delivering lobar doses of 70 and 120 Gy, respectively, display hepatic toxicity similar to 40-Gy fractionated external-beam radiotherapy. We investigated how the lower number of glass microspheres could induce a sufficiently nonuniform dose distribution explaining this paradox. Methods: Microscale dosimetry was assessed in the realistic liver model developed by Gulec et al. but using the Russell's dose deposition kernel. A lattice of hexagonal prisms re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 14 publications
4
71
1
1
Order By: Relevance
“…Similar levels of clustering were also shown in simulations of GMS in different arterial tree models when the difference in number of spheres is taken into account [41].…”
Section: Microsphere Distributionsupporting
confidence: 52%
See 2 more Smart Citations
“…Similar levels of clustering were also shown in simulations of GMS in different arterial tree models when the difference in number of spheres is taken into account [41].…”
Section: Microsphere Distributionsupporting
confidence: 52%
“…A similar MC study showed that the non-uniform trapping produced by GMS transport in a simulated arterial tree may explain their lower toxicity per Gy [41]. They showed a highly asymmetric spread of dose distribution, with 17% of lobules receiving < 40 Gy.…”
Section: Microsphere Distributionmentioning
confidence: 87%
See 1 more Smart Citation
“…Lam et al [8] also rightly underlined the fact that dosimetric results and threshold should be interpreted with caution, given the numerous confounding factors that can be encountered, such as the different radiobiological properties of available 90 Y-loaded microspheres [14], histological tumour types with different radiosensitivity profiles, underlying hepatic disease, the different dosimetric tools used, as mentioned above, and so on. These points must be kept in mind when analysing study results.…”
mentioning
confidence: 99%
“…In a recent study (8), we showed by Monte Carlo simulations that the random and asymmetric spreading of microspheres between the daughter vessels at the nodes of the hepatic arterial tree induces a large nonuniformity of microscale dose distribution as observed on PET (9,10) (Fig. 1).…”
mentioning
confidence: 99%